Evaluación de la comprensión de las fórmulas enlace-línea en un curso de química orgánica universitaria - Santisteban Salazar, Nelson César (2020)
The level of understanding of the line-link formulas was determined for the representation of molecular formulas of organic compounds. The research was observational, descriptive and cross-sectional, and the sample was 53 students from the Polytechnic Amazonian University of Bagua Grande, enrolled in the organic chemistry course of the 2018-I cycle, intentionally selected. Of the total students located in the high group, 100% (13) corresponded to Agronomic Engineering, while at this same level 82% (18) of section A and 89% (16) of section B of Nursing were located. The lowest level of hits corresponded to the order of the elements in the molecular formula, followed by the number of hydrogens. It was concluded that the students had a high percentage of correct answers when writing the molecular formulas as a result of a high level of understanding of the line- link formulas.